2021
DOI: 10.3390/ijerph18010297
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 and Trace Elements in Underground Shopping Districts in the Seoul Metropolitan Area, Korea

Abstract: We measured PM2.5 in 41 underground shopping districts (USDs) in the Seoul metropolitan area from June to November 2017, and associated 18 trace elements to determine the sources and assess the respiratory risks. The PM2.5 concentrations were 18.0 ± 8.0 μg/m3 inside USDs, which were lower than 25.2 ± 10.6 μg/m3 outside. We identified five sources such as indoor miscellanea, soil dust, vehicle exhaust/cooking, coal combustion, and road/subway dust, using factor analysis. Almost 67% of the total trace element co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 86 publications
2
2
0
Order By: Relevance
“…Coal is one of the materials of the earth's crust, the footprint of coal combustion emissions can be characterized by other dominant elements in the ambient air of this region, such as Zn and Ti. Similar to the research conducted by [20], which also found Zn abundance in PM2.5 samples, this element can be predicted as a marker of fossil fuel combustion. In addition, it is known that Ti is the most dominant element in PM2.5, reaching 50% of the total elements characterized [20].…”
Section: Heavy Metal Characterization In Pm25 Dustsupporting
confidence: 85%
See 1 more Smart Citation
“…Coal is one of the materials of the earth's crust, the footprint of coal combustion emissions can be characterized by other dominant elements in the ambient air of this region, such as Zn and Ti. Similar to the research conducted by [20], which also found Zn abundance in PM2.5 samples, this element can be predicted as a marker of fossil fuel combustion. In addition, it is known that Ti is the most dominant element in PM2.5, reaching 50% of the total elements characterized [20].…”
Section: Heavy Metal Characterization In Pm25 Dustsupporting
confidence: 85%
“…Similar to the research conducted by [20], which also found Zn abundance in PM2.5 samples, this element can be predicted as a marker of fossil fuel combustion. In addition, it is known that Ti is the most dominant element in PM2.5, reaching 50% of the total elements characterized [20]. Based on [17] and [19], Ti elements can come from soil dust or earth crust elemet.…”
Section: Heavy Metal Characterization In Pm25 Dustsupporting
confidence: 85%
“…Exposure to most of these elements can severely affects human health, causing several cardiovascular diseases and other adverse health effects. [11][12][13] Furthermore, carbonaceous aerosol including organic carbon (OC) and elemental carbon (EC) derived from the combustion of fossil fuels and biomass burning are another toxic components of PM 2.5 . 14,15 In addition, carbonaceous aerosol, especially EC, plays a vital role as a climate-forcing agent with strong warming potential.…”
Section: Introductionmentioning
confidence: 99%
“…The law is known as the “Indoor Air Quality Control Act”, in which USDs are classified as “public-use facilities”, and hazardous materials such as formaldehyde, total volatile organic compounds (TVOC), particulate matter with an aerodynamic diameter < 10 µm (PM 10 ) and <2.5 µm (PM 2.5 ), and CO 2 are designated as target substances with the objective of managing indoor air quality. Public-use facilities are defined as facilities that are utilized by unspecified groups of people [ 4 ]. In South Korea, public-use facilities are classified into 24 types, and the concentrations of hazardous substances are classified and managed based on the characteristics of each facility type.…”
Section: Introductionmentioning
confidence: 99%